Blogging Back then: Annotative journalism in I.F. Stone's Weekly and Talking Points Memo. (January 2015) - Graves, Lucas
This article develops the concept of 'annotative journalism' through a close review of two muckraking investigations, 50 years apart, by the newsletter I.F. Stone's Weekly and the website Talking Points Memo. These cases stand out in hindsight as investigative coups, though neither relied on the tools we associate with that kind of journalism: anonymous sources, secret documents, and so on. Instead, both investigations proceeded mainly through the analysis of published texts, in particular news reports, in light of a wider media and political critique. Annotative journalism unsettles core practices and assumptions of objective reporting. It rejects narrative coherence in favor of a set of critical textual practices, revealing reporting routines to the reader and building explicit arguments from and about the work of other journalists. And it troubles the professional distinction between reporting and opinion; these 'scoops' came through, not in spite of, the politics of the journalists who worked on them.